MAINTAINING VITAL SIGNS OF THE TRANSPLANTED KIDNEY. - Ismoilov Ibodjon Imomjonovich (Scholar Express Journals, 2023)
Treatment of chronic renal failure is one of the medical and social problems for modern modern medicine. There are now a growing number of methods for the kidney and its maintenance, for example: Temporary renal hemodialysis, as well as kidney transplantation, which leads to an increase in the life expectancy of patients. But not always. At present, the number of patients in need of kidney transplantation and the number of transplant options are increasing. This is primarily due to acute and chronic renal failure, and secondly, due to the increased number of transplants.
Keywords: organ transplant; acute rejection; immunological tolerance